Genome-wide identification of long non-coding RNA genes and their association with insecticide resistance and metamorphosis in diamondback moth, Plutella xylostella. Issue 1 (December 2017) - Liu, Feiling; Guo, Dianhao; Yuan, Zhuting; Chen, Chen; Xiao, Huamei
Abstract Long non-coding RNA (lncRNA) is a class of noncoding RNA >200 bp in length that has essential roles in regulating a variety of biological processes. Here, we constructed a computational pipeline to identify lncRNA genes in the diamondback moth (Plutella xylostella ), a major insect pest of cruciferous vegetables. In total, 3, 324 lncRNAs corresponding to 2, 475 loci were identified from 13 RNA-Seq datasets, including samples from parasitized, insecticide-resistant strains and different developmental stages. The identifiedP. xylostella lncRNAs had shorter transcripts and fewer exons than protein-coding genes. Seven out of nine randomly selected lncRNAs were validated by strand-specific RT-PCR. In total, 54–172 lncRNAs were specifically expressed in the insecticide resistant strains, among which one lncRNA was located adjacent to the sodium channel gene. In addition, 63–135 lncRNAs were specifically expressed in different developmental stages, among which three lncRNAs overlapped or were located adjacent to the metamorphosis-associated genes. These lncRNAs were either strongly or weakly co-expressed with their overlapping or neighboring mRNA genes. In summary, we identified thousands of lncRNAs and presented evidence that lncRNAs might have key roles in conferring insecticide resistance and regulating the metamorphosis development inP. xylostella .